Concussion BASICS II: Baseline serum biomarkers, head impact exposure, and clinical measures. (4th December 2018) - Asken, Breton M.; Bauer, Russell M.; DeKosky, Steven T.; Houck, Zachary M.; Moreno, Charles C.; Jaffee, Michael S.; Dubose, Dewayne N.; Boone, Jonathan K.; Weber, Arthur G.; Clugston, James R.
Abstract : Objective: To examine the effect of concussion history and cumulative exposure to collision sports on baseline serum biomarker concentrations, as well as associations between biomarker concentrations and clinical assessments. Methods: In this observational cohort study, β-amyloid peptide 42 (Aβ42 ), total tau, S100 calcium binding protein B (S100B), ubiquitin carboxy-terminal hydrolyzing enzyme L1 (UCH-L1), glial fibrillary acidic protein, microtubule associated protein 2, and 2′, 3′-cyclic-nucleotide 3′-phosphodiesterase serum concentrations were measured in 415 (61% male, 40% white, aged 19.0 ± 1.2 years) nonconcussed collegiate athletes without recent exposure to head impacts. Regression analyses were used to evaluate the relationship between self-reported history of concussion(s), cumulative years playing collision sports, clinical assessments, and baseline biomarker concentrations. Football-specific analyses were performed using a modified Cumulative Head Impact Index. Clinical assessments included symptom, cognitive, balance, and oculomotor tests. Results: Athletes with a greater number of concussions had a higher baseline Aβ42 concentration only (ρ = 0.140, p = 0.005, small effect size). No biomarker concentrations correlated with cumulative exposure to collision sports. Race status fully mediated the correlations of S100B, UCH-L1, and Aβ42 with cognitive scores. Football exposure, specifically, was not associated with serum biomarker concentrations or clinical assessment scores based on the modified Cumulative Head Impact Index. Conclusion: Concussion-related serum biomarkers showed no consistent association with concussion history, cumulative exposure to collision sports, or clinical assessments in a sample of healthy collegiate athletes. Serum Aβ42 concentrations could increase following multiple previous concussions. Considering race status is essential when investigating links between biomarkers and cognition. The biomarkers studied may not detect residual effects of concussion or repetitive head impact exposure in otherwise asymptomatic collegiate athletes without recent exposure to head impacts. Much more research is needed for identifying reliable and valid blood biomarkers of brain trauma history.